FLEPVAR 2013 (Flemish Pass Variability 2013) - Cruise No. MSM27 - April 19 - May 06, 2013 - St. John's (Canada) - St. John's (Canada) ... - Kieke, Dagmar; De Abreu Nunes, Nuno; Grieshaber, Björn; Hinrichs, Claudia; Horn, Myriel; Jochumsen, Kerstin; Mertens, Christian; Moritz, Martin; Peters, Maike; Schneider, Linn; Sültenfuß, Pia; Varotsou, Eirini; et al. (DFG-Senatskommission für Ozeanographie, 2014)
Cruise MSM-27 was dedicated to investigating the circulation and water mass structure at the western rim of the subpolar North Atlantic. Particular focus was put on the water mass export through Flemish Pass (FP), export within the Deep Western Boundary Current (DWBC) flowing around Flemish Cap (FC), and the circulation system in the southern Orphan Basin. Among the objectives of cruise MSM-27 was the exchange of two deep-sea mooring arrays installed at about 47°N in Flemish Pass and in the DWBC east of Flemish Cap. The FP array aims at measuring the velocity structure and temperature and salinity of Labrador Sea Water (LSW) exported through Flemish Pass. The DWBC array is a full water-column mooring array. It serves to establish time series of volume transport and water mass properties related to the different components contributing to the DWBC and the North Atlantic Current (NAC). Due to the loss of one DWBC mooring the entire DWBC array could not be deployed again. As a further consequence, deployment of ... : MARIA S. MERIAN-Berichte ...